BIOSTATISTICAL ESTIMATION OF WEEDS SURVEYED IN BAGALKOT KARNATAKA - T. C. GOPAL, (The Bioscan, 2023)
The current study encountered with 120 species under the 101 genera belonging to 36 families. Among 36 families, Asteraceae, Poaceae and Fabaceae were dominated with highest number of species. Among 36 families, Asteraceae, Poaceae and Fabaceae were dominated with 20, 17 and 13 respectively. A few species, including Amaranthus polygonoides, Tridax procumbens, and Parthenium hysterophorus, were determined to be the most regenerative and dominant species in the research region out of all the species. Based on our findings, we have concluded that the study area offers an environment that is conducive to the growth and development of the weed species. Additionally, it is advised that researchers figure out how to get rid of or manage these weeds in the agricultural ecosystem.